iMSL: Malay sign language for the deaf and hearing-impaired - Muhd Darus, Norida; Abdullah, Nur Tahrina; Abdul Mutalib, Ariffin (2012)
Malay Sign Language (MSL)or Bahasa Isyarat Malaysia is a language that has been used by the deaf people in Malaysia. The deaf and hearing-impaired people go to special schools to learn the MSL. Incurrent age, technology could be utilized for the purpose of providing MSL course for the hearing-impaired people and their stakeholders. With the provision of the technology-based MSL course,learning MSL not only happen in schools, but also at home, or anywhere. This makes the learning activity pervasive.Based on that argument, this study aims at proposing a model for an interactive MSL (iMSL). Accordingly, this paper discusses the background concept for the needs and design of the iMSL. It contains the problem that lead for the iMSL, and activities and techniques to involve.